Research on the differences in the spatial distribution of land resource security in North China based on the DPSIRM model - Lu, Honglei; Ge, Kunyin (Frontiers in Earth Science, 2025)
Land ecological safety has become a key issue in the pursuit of ethical and sustainable land use. This study, based on the DPSIRM (Driving force–Pressure–State–Impact–Response–Management) framework, employed the entropy weight TOPSIS model and the grey relational analysis model to evaluate the ecological safety level of land resources (ESLR) in North China from 2012 to 2021. The results indicate that overall ESLR has improved, following three distinct phases of stability, substantial growth, and slight decline, while significant regional disparities remain, with Tianjin (0.4495) at a relatively precarious level and Hebei (0.5966) in a more favourable state. Spatial differences are largely shaped by geographical and resource conditions, and among all influencing factors, land resource pressure shows the strongest correlation with ESLR. These findings suggest that although ecological safety of land resources in North China is progressing, uneven regional development highlights the need for targeted strategies to reduce land-use pressures and promote balanced, sustainable land management.